E-055 Internal carotid artery reconstruction with flow diverting stents in the treatment of acute ischemic stroke: technical considerations and medical management. (23rd July 2022) - Orru, E; Bounni, F; Marosfoi, M; Patel, N; Wakhloo, A
Abstract : Introduction: Extracranial internal carotid artery (ICA) dissections can cause stroke in a relatively young patient population. Acute endovascular reconstruction might be needed for cases with concomitant large vessel occlusion (LVO) or with a symptomatic hemispheric perfusion deficit. Tortuous cervical ICAs, often associated with dissection, might limit applicability of stiff carotid stents and require utilization of more flexible flow diverting stents (FDS). We present clinical results and technical considerations for the use of FDS in a series of patients treated for symptomatic ICA dissection. Materials and Methods: We retrospectively reviewed all cases of symptomatic ICA dissections that presented at our hospital in 24 months and reviewed technical aspects and clinical outcomes of those that underwent acute reconstruction by FDS. Results: Six males (range: 37–66 years) underwent acute ICA reconstruction with FDS for treatment of a symptomatic dissection. In 3 (50%) cases the dissected segment had a complete loop. Five (80%) patients had concomitant intracranial LVO, 1 had a large area of hypoperfusion on CT imaging. ICA luminal restoration was achieved in all cases. An average of 2 FDS were deployed telescopically to cover the dissection. Balloon angioplasty was performed in two cases to improve opening of the implant. Adjunctive carotid stents were deployed in all cases to secure the proximal end of the FDS. LVOs were addressed after ICA reconstructions by combined technique and ingestion of the stentriever in the aspiration catheter, that was advanced within the construct and positioned distally to it without issue in all cases (TICI scores: 2b-3). All patients received intra-operative eptifibatide, bridged subsequently to dual antiplatelet therapy (aspirin + ticagrelor). Acute, non-occlusive in-stent thrombus was noted in 2 cases, while wire access was lost in one case, significantly increasing operative time. Hemorrhagic transformation of an acute infarct was seen in 2 (33%) patients. A good outcome (mRS 0–2 at 90 days) was achieved in 5 (83%) patients, while one died of malignant brain edema shortly after intervention. Imaging follow-up was available for 4/5 surviving patients (80%, median: 18 months) and showed complete stent patency. Conclusions: FDS appear to be a safe and effective tool for reconstruction of a symptomatic dissection in tortuous cervical ICAs. Their flexibility allows conformation to complex anatomies and they can be traversed multiple times by aspiration catheters/stentrievers. We found excellent patency at follow up. The unique challenges posed by utilization of high-profile stents in acute stroke require appropriate technical execution and medical management. Disclosures: E. Orru: None. F. Bounni: None. M. Marosfoi: None. N. Patel: None. A. Wakhloo: 1; C; Philips medical. 2; C; Stryker, Phenox. 4; C; InNeuroCo, EpiEP, Neural Analytics, ThrombX.